Protected areas slow declines unevenly across the tetrapod tree of life - Justin Nowakowski, A.; Watling, James I.; Murray, Alexander; Deichmann, Jessica L.; Akre, Thomas S.; Muñoz Brenes, Carlos L.; Todd, Brian D.; McRae, Louise; Freeman, Robin; Frishkoff, Luke O. (Nature (London), 2023)
Protected areas (PAs) are the primary strategy for slowing terrestrial biodiversity loss. Although expansion of PA coverage is prioritized under the Convention on Biological Diversity, it remains unknown whether PAs mitigate declines across the tetrapod tree of life and to what extent land cover and climate change modify PA effectiveness 1 , 2 . Here we analysed rates of change in abundance of 2,239 terrestrial vertebrate populations across the globe. On average, vertebrate populations declined five times more slowly within PAs (−0.4% per year) than at similar sites lacking protection (−1.8% per year). The mitigating effects of PAs varied both within and across vertebrate classes, with amphibians and birds experiencing the greatest benefits. The benefits of PAs were lower for amphibians in areas with converted land cover and lower for reptiles in areas with rapid climate warming. By contrast, the mitigating impacts of PAs were consistently augmented by effective national governance. This study provides evidence for the effectiveness of PAs as a strategy for slowing tetrapod declines. However, optimizing the growing PA network requires targeted protection of sensitive clades and mitigation of threats beyond PA boundaries. Provided the conditions of targeted protection, adequate governance and well-managed landscapes are met, PAs can serve a critical role in safeguarding tetrapod biodiversity. An analysis of 2,239 terrestrial vertebrate populations shows that they decline more slowly in protected areas than outside protected areas, but the benefits vary across vertebrate classes and depend on the regional context of the protected area.